Guía básica de educación sexual para prevenir el abuso sexual infantil en los estudiantes de quinto a de la escuela de educación básica ciudad de Loja, 2019-2020. - Valdivieso Cevallos, Maria Salome (2020)
Sexual abuse can cause physical, psychological and social problems, the most convenient thing is to work from prevention (before), for which an intervention proposal was designed with the main objective: to implement the basic guide for Sexual Education to prevent sexual abuse. child sexual abuse in fifth-year students of the Ciudad de Loja basic education school, 2019-2020, which was carried out on a sample of 33 minors. The research corresponds to a quantitative approach, and the scientific method was used as the main method and the inductive - deductive, analytical - synthetic and descriptive as auxiliary methods, the Jorge Prudence Test was used as an evaluation instrument (pre-post test) Luzoro, in the pre-test the following results were obtained: 42% of Reckless students, 46% Little Precavidos and 12% as Prudentes. This means that the students did not have the necessary tools to protect themselves from abusive situations, which leaves the child exposed to possible sexual abuse. After the intervention proposal, the post-test was applied, in which the following results were obtained: 5% Reckless, 11% Slightly Cautious and 84% Prudent. In conclusion, the implementation of the basic guide, had a positive advantage and is recognized by means of the Student's T statistical test, thus validating the proposal, obtaining a level of confidence of 95% and with a degree of error of 5%, which indicating that the alternative hypothesis is accepted and therefore the null hypothesis is rejected. Therefore, it is recommended that the Ciudad de Loja school continue implementing the activities proposed in the basic guide to sexual education for the prevention of child sexual abuse in fifth grade of basic education.